THE DESIGN OF MANAGEMENT INFORMATION SYSTEMS AT JAMI KAUTSAR MOSQUE - Sri Rezeki Candra Nursari; Prasetyo Linuwih (LPPM STMIK Pringsewu, 2021)
This research is motivated by the management of the Jami Al-Kautsar Mosque in Depok which has not been properly recorded and the data storage is scattered. These constraints have the potential for data loss and inaccurate information and a process taking a long time to produce such information. In this study, the data collection techniques used are observation, interviews and literature study. The information system built uses the waterfall method as a software development or Software Development Life Cycle (SDLC) using object-oriented design of the Unified Modeling Language (UML) and testing using Black Box. The process in this study includes the process of managing activities, managing the mosque, inventory, finances and goods (income and expenditure). The results of research implemented by the author on the Management Information System of the Jami Al-Kautsar Mosque is a system that can provide information on the management of activities, mosque administrators (human resources), inventory, finances and goods (income and expenditure) as well as communicative and informative reports so that they can make evaluation materials and transparent accountability reports from the management to all congregations of the Jami Al-Kautsar Mosque. User satisfaction with the evaluation information system uses the five-category Black Box test and produces a good information system. Three categories of Black Box testing are no errors in functions, database access and structure and system performance above 60%.